2021
DOI: 10.1186/s12882-021-02534-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of AKI care bundles on kidney and patient outcomes in hospitalized patients: a systematic review and meta-analysis

Abstract: Background A bundle of preventive measures can be taken to avoid acute kidney injury (AKI) or progression of AKI. We performed a systematic review and meta-analysis to evaluate the compliance to AKI care bundles in hospitalized patients and its impact on kidney and patient outcomes. Methods Randomized controlled trials, observational and interventional studies were included. Studied outcomes were care bundle compliance, occurrence of AKI and modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…Limited systematic studies have been conducted to evaluate the effectiveness of AKI care bundles; prior our study, only Schaubroeck et al [ 42 ] presented a comprehensive review and meta-analysis on patient outcomes associated with AKI care bundle implementation. In particular, we extensively searched Chinese databases in order to include similar studies that could potentially serve as professional guidelines for Chinese hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Limited systematic studies have been conducted to evaluate the effectiveness of AKI care bundles; prior our study, only Schaubroeck et al [ 42 ] presented a comprehensive review and meta-analysis on patient outcomes associated with AKI care bundle implementation. In particular, we extensively searched Chinese databases in order to include similar studies that could potentially serve as professional guidelines for Chinese hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…MI type NSTEMI 184 (22) 214 (20) 315 (21) 258 (23) 62 (25) 54 (18) 78 ( 19 482 (32) 264 ( 24) 66 ( 27)…”
Section: Discussionunclassified
“…Similar to the IMPROVE AKI trial findings, the systematic review and meta-analysis by Schaubroeck and colleagues 2021 found that when AKI bundles were implemented into routine clinical practice, they were associated with reductions in moderate-to-severe AKI. 32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review and meta-analysis [92] suggests that implementation of AKI care bundles in hospitalized patients reduces moderate to severe AKI, but that the overall compliance to AKI care bundles is highly variable.…”
Section: Novel Biomarkers and Their Possible Impact On Definition And...mentioning
confidence: 99%